EPIDEMIOLOGI MANAJERIAL DAN DETERMINAN SOSIAL PADA LAYANAN PUBLIK: TINJAUAN LITERATUR DAMPAK PELATIHAN, PEMBINAAN, DAN KETERLIBATAN KARYAWAN TERHADAP KUALITAS PELAYANAN MELALUI PERSEPSI KEBIJAKAN MUTU DI RSUD PATUT PATUH PATJU LOMBOK BARAT PROVINSI NTB - Desak Gede Sri Baktiasih; Yuly Peristiowati (Bajang Institute, 2026)
Background: Service quality in government hospitals is often influenced by managerial dynamics and the complexity of social determinants. At the Patut Patuh Patju Regional General Hospital (RSUD) in West Lombok, West Nusa Tenggara Province, the integration of managerial epidemiology and human resource (HR) development has become the primary key to addressing public service challenges. Objective: This study aims to analyze the impact of training, coaching, and employee engagement on service quality, with quality policy perception as a mediating variable. Methods: This research employs a Systematic Literature Review (SLR) approach. A literature search was conducted via Scopus and Google Scholar databases covering the period 2014-2024. Inclusion criteria focused on studies discussing HR management in the public health sector and hospital quality management. Results: Findings indicate that training and coaching significantly strengthen both technical and psychological competencies of employees. Employee engagement acts as a catalyst, transforming quality policies from mere formalities into tangible service behaviors. A positive perception of quality policy is proven to mediate the relationship between managerial interventions and service quality improvement. Conclusion: Strengthening internal managerial aspects is a crucial strategy for Patut Patuh Patju Regional General Hospital (RSUD) in West Lombok, West Nusa Tenggara Province to overcome social determinant barriers and deliver quality, responsive healthcare services.